Analytical study of RUNX1-RUNXT1, PML-RARA, CBFB-MYH11, BCR-ABL1p210, and KMT2-MLLT3 in Mexican children with acute myeloid leukemia: A multicenter study of the Mexican interinstitutional group for the identification of the causes of childhood leukemia (MIGICCL) - Sepúlveda-Robles, Omar; Jiménez-Hernández, Elva; Domínguez-Catzín, Victoria; Gómez-Flores, Eber; Martín-Trejo, Jorge Alfonso; Flores-Lujano, Janet; Torres-Nava, José Refugio; Núñez-Enríquez, Juan Carlos; De Ita, Marlon; Medina-Sanson, Aurora; Mata-Rocha, Minerva; Morales-Castillo, Blanca Angelica; et al. (Frontiers in Pediatrics, 2022)
Background: The distribution of RUNX1-RUNXT1, PML-RARA, CBFB-MYH11, BCR-ABL1p210, and KMT2A-MLLT3 in the pediatric population with acute myeloid leukemia (AML) in many countries of Latin America is largely unknown. Therefore, we aimed to investigate the frequency of these fusion genes in children with de novo AML from Mexico City, which has one of the highest incidence rates of acute leukemia in the world. Additionally, we explored their impact in mortality during the first year of treatment. Methods: We retrospectively analyzed the presence of RUNX1-RUNXT1, PML-RARA, CBFB-MYH11, BCR-ABL1p210, and KMT2A-MLLT3 by RT-PCR among 77 patients (<18 years) diagnosed with de novo AML between 2019 and 2021 in nine Mexico City hospitals. Results: The overall frequency of the fusion genes was 50.7%; RUNX1-RUNXT1 (22.1%) and PML-RARA (20.8%) were the most prevalent, followed by CBFB-MYH11 (5.2%) and BCR-ABL1p210 (2.4%). KMT2A-MLLT3 was not detected. Patients with PML-RARA showed the lowest survival with high early mortality events. However, more studies are required to evaluate the impact of analyzed fusion genes on the overall survival of the Mexican child population with AML. Conclusion: The pediatric population of Mexico City with AML had frequencies of AML1-ETO, PML-RARA, CBFB-MYH11, and BCR-ABL1p210 similar to those of other populations around the world. Patients with BCR-ABL1p210 and CBFB-MYH11 were few or did not die, while those with MLL-AF9 was not detected. Although patients with PML-RARA had a low survival and a high early mortality rate, further studies are needed to determine the long-term impacts of these fusion genes on this Latino population.